Effects of Heat and Humidification on Aerosol Delivery during Auto-CPAP noninvasive Ventilation - Marwa Mohsen; Ahmed A Elberry; Abeer Salah Eldin; Raghda RS Hussein; Mohamed EA Abdelrahim (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2017)
Objective: Although, the use of humidification during non-invasive ventilation (NIV) is an important factor in decreasing nasal airway resistance and assuring patient's comfort and adherence; many in-vitro studies recommend switching off the humidifier while delivering aerosol to NIV patients. The aim of the study was to in-vivo determine the effect of humidification on salbutamol delivered via different  inhalation  devices  to  chronic  obstructive  pulmonary  disease  (COPD)  patients  using  automatic continuous positive airway pressure (Auto-CPAP). Method: Aerosol delivery to NIV COPD patients by Aerogen Solo vibrating mesh nebuliser (VMN), Jet nebuliser (JET) and a metered dose inhaler (MDI) with AeroChamber MV spacer (AC) were compared with and without humidification. Auto-CPAP was adjusted at non-invasive ventilation mode with the integrated heated humidifier (IHH), as a source of humidity. The heater was set to the default setting 3, equivalent to 50ºC. Urine samples, 30 minutes and 24 hours post inhalation, as an index of the relative pulmonary and systemic bioavailability respectively, were provided by subjects and aliquots were retained for salbutamol analysis using solid phase extraction and high performance liquid chromatography (HPLC). Results: There  was  no  significant  difference  in  the  urinary  excreted  salbutamol  post  inhalation between the humidified and dry conditions. However, there was a significant difference between devices.The MDI with AC spacer had the highest percentage of 30 minutes urinary excreted salbutamol and JET had the lowest (p<0.01). VMN the highest percentage of 24 hours urinary excreted salbutamol and JET had the lowest but the difference was not significant. Conclusion: Significance of switching off humidity during aerosol delivered to ventilated patient was not as previously shown in in-vitro literatures. We recommend delivering aerosol medication to Auto-CPAPNIV patient using humidity without fear of lower delivery